The Impact of Social Media Influencer on Customer’s Attitude - Wan Nor Hidayah Wan Afandi; Nathasya Mohd Kamal; Nurul Zaitul Itri Alias (Human Sustainability Procedia, 2022)
Social media influencer is becoming the spokesperson for brands nowadays. This study investigates the impact of social media influencer on consumer’s attitude which focuses on source attractiveness and product match-up. This study applied Social Learning Theory and Social Cognitive Theory by Albert Bandura in order to explain the relationship between variables. This quantitative research collected its data through online survey which was distributed to 120 respondents from Kolej Universiti Poly-Tech MARA, Kuala Lumpur. The findings show that relationship between variables are significant. Social media influencer that have the characteristics such as source attractiveness and product match-up are more likely to change the consumer attitude toward certain brands. Hence, this study contributes to the field of communication through the establishment of a more comprehensive variables related to social media influencer in changing customer’s attitude.